Dynamic Update for Operating Systems - Baumann, Andrew (The University of New South Wales, 2007)
Patches to modern operating systems, including bug fixes and security updates, and the reboots and downtime they require, cause tremendous problems for system users and administrators. The aim of this research is to develop a model for dynamic update of operating systems, allowing a system to be patched without the need for a reboot or other service interruption. In this work, a model for dynamic update based on operating system modularity is developed and evaluated using a prototype implementation for the K42 operating system. The prototype is able to update kernel code and data structures, even when the interfaces between kernel modules change. When applying an update, at no point is the system's entire execution blocked, and there is no additional overhead after an update has been applied. The base runtime overhead is also very low. An analysis of the K42 revision history shows that approximately 79% of past performance and bug-fix changes to K42 could be converted to dynamic updates, and the proportion would be even higher if the changes were being developed for dynamic update. The model also extends to other systems such as Linux and BSD, that although structured modularly, are not strictly object-oriented like K42. The experience with this approach shows that dynamic update for operating systems is feasible given a sufficiently-modular system structure, allows maintenance patches and updates to be applied without disruption, and need not constrain system performance.